PERAN TRANSFORMASI DIGITAL DALAM EKOSISTEM INOVASI BERKELANJUTAN: SYSTEMATIC LITERATURE REVIEW BAGI INOVATOR - Fathussyaadah, Eva (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to identify, evaluate, and integrate various literatures on organizational growth strategies through the Growth with Next Level Innovator conceptual framework. Amidst the dynamics of the Fourth Industrial Revolution (4IR), organizations face the challenge of transcending traditional operational efficiency toward more complex innovation ecosystems. Utilizing the Systematic Literature Review (SLR) method on indexed scientific databases for the 2016–2026 period, this study synthesizes findings from previously fragmented innovation sub-domains. The analysis reveals that advanced (Next Level) growth depends on systemic synergy between four main pillars: platform-based digital entrepreneurship, creative methodologies (design thinking and foresight), sustainable innovation practices (eco-innovation), and adaptive governance policies, including Intellectual Property Rights (IPR) protection. Research findings indicate that digital platforms serve as the primary growth accelerators, while the integration of foresight enables organizations to proactively navigate market uncertainties. However, barriers such as capital constraints and regulatory inconsistencies remain significant challenges, particularly for SMEs. This research provides a theoretical contribution in the form of an integrative working model that links digital capacity with environmental responsibility and strategic policy. Practically, this framework serves as a guide for organizational leaders in building collaborative and sustainable value ecosystems.